Design and fabrication of cold thermal energy storage tank to operate in water chiller air-conditioning system - Trần Thanh Huy; Nguyễn Xuân Viên; Đoàn Minh Hùng (Journal of Technical Education Science, 2020)
This paper presents a study on the design and fabrication of cold thermal energy storage tank to operate in Water Chiller air-conditioning system with cooling capacity of 360.000 BTU/h. Water is used as the heat transfer fluids in cold storage tank. The polyvinyl chloride pipe (PVC) is used to fabricate the heat exchanger. In this work, the investigation of system properties is based on an experimental study. The results indicate the operation properties such as the cold storage tank temperature in load-charging, heat transfer fluids temperature in load-discharging, load-discharging time. In addition, the results also show the heat transfer efficiency of heat exchanger in the cold thermal energy storage tank is acceptable. The temperature difference of the inlet and outlet heat transfer fluid in heat exchanger is maintained from 3 to 4 ºC. This is a suitable design for use cold thermal storage system in cooling applications.